PENGEMBANGAN MEDIA VIDEO ANIMASI DENGAN BERBANTUAN CANVA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII PADA MATERI DAMPAK SOSIAL INFORMATIKA DI SMP - Sarifah Aini; Darmansyah (STKIP Subang, 2025)
This study aims to develop Canva-assisted Animated Video Media to Increase Learning Motivation of Grade VII Students on the Social Impact of Informatics Material in Junior High Schools that is valid and practical. This research is motivated by teachers who are less than optimal in utilizing existing technology in schools, learning that is still monotonous and the lack of learning media in schools so that students are less motivated to learn. This study uses a Research & Development (R&D) approach with a 4D development model that includes 4 stages, namely define, design, develop, and disseminate. The results of this study indicate that the assessment of the material validator obtained an average score of 4.53 with the category